Pendekatan Komunikasi Islam pada Nilai Mauizah Hasanah: (Telaah Konsep dan Aplikasi Dalam Kehidupan) - Junaidi (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
Many of Islamic concepts are not implemented in daily life. This is due to the way the delivery of religious messages is still not quite right, God says Q. An-Nahl, 125. "Call your people away with your wisdom and good teaching". The concept of Mauizatul Hasanah becomes important to be studied in the aspect of human communication. This paper will be analyzed using descriptive analysis method. The result was found that the approach of mauizatul hasanah was by conveying good messages that reflected the Prophet's self and the pious people in order to lead to good deeds. Islam teaches doing good deeds, polite behavior and knowing the first order of life towards the happiness of the world and the hereafter.